Peran Pendidikan Agama Islam dalam Membentuk Karakter Generasi Muda di Era Modern - Mulia Rejeki (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the role of Islamic Religious Education in shaping the character of young generations in the contemporary era. Islamic Religious Education is not only focused on cognitive aspects but also emphasizes moral, spiritual, and social development. The rapid development of technology and globalization has influenced the lifestyle and mindset of youth, creating challenges in maintaining ethical values and noble character. This research aims to analyze how Islamic Religious Education contributes to the formation of students’ character, including honesty, responsibility, discipline, tolerance, and social awareness. The research method uses a qualitative descriptive approach through literature review and analysis of relevant educational practices. The results show that effective Islamic Religious Education can strengthen students’ moral awareness, develop positive behavior, and build spiritual intelligence. Teachers play a significant role as role models in integrating Islamic values into daily life. Therefore, strengthening curriculum, learning methods, and collaboration between schools, families, and communities is essential to optimize the role of Islamic Religious Education in forming a morally upright and responsible young generation.